P022 Checkpoint inhibitors activate store-operated CA2+ entry and ERK1/2 signalling and promote TH17 differentiation. (21st February 2018) - Zapp, B; Lehmkuhl, P; Schulze-Koops, H; Skapenko, A
Abstract : Introduction: Anti-tumour therapy with immune checkpoint inhibitors for programmed-death 1 receptor (PD1), such as nivolumab is often accompanied by immune-related adverse events (irAE). The cellular and molecular mechanisms underlying this phenomenon are not defined yet. Interaction of PD-1 with its ligand (PD-L1) mediates potent inhibitory signals to hinder proliferation and effector function of T cells. Interruption of PD1:PD-L1 interaction by nivolumab during anti-tumour therapy might therefore amplify T cell receptor (TCR) signalling and facilitate the development of a pro-inflammatory autoimmune response. Objectives: To investigate the impact of PD1 inhibition on intracellular signalling mechanisms down-stream of the TCR such as calcium (Ca 2+ ) influx and activation of mitogen-activated protein kinases (MAPK) pathway and to assess the effect of PD1 inhibition on T cell effector function by evaluating the cytokine profile of the nivolumab-treated T cells. Methods: CD4 memory T cells were stimulated with anti-CD3 and anti-CD28 in the presence of nivolumab for 24 hour. Afterwards intracellular Ca 2+ influx in response to ionomycin was assessed by flow cytometry following loading the cells with Fluo-8. Expression of proteins involved in store-operated Ca 2+ entry (SOCE), stromal activation molecule (STIM) 1, an activator of Ca 2+ release-activated Ca 2+ (CRAC) channels, and Orai1, a component of CRAC channels was determined by TaqMan real-time PCR. Phosphorylation of extracellular signal-regulated kinase 1 and 2 (Erk1/2) in response to anti-CD3/28 was determined by intracellular flow cytometry. The cytokine profile of nivolumab-treated cells was assessed after four-day culture by intracellular flow cytometry. Results: Treatment of CD4 T cells with nivolumab led to a pronounced increase of the ionomycin-mediated Ca 2+ influx. At the same time expression of SOCE proteins, STIM1 and Orai1, was significantly up regulated in the nivolumab-treated cells. Phosphorylation of Erk1/2 in response to short anti-CD3/CD28 restimulation was almost twice as high in CD4 T cells cultured with as without nivolumab. Finally nivolumab-treated cells contained higher frequencies of IL-17-producing T cells (Th17 cells). Conclusions: Interruption of PD1:PD-L1 interaction by nivolumab activate SOCE and promotes Erk1/2 activation. Both T cell signalling pathways are essential for a proper mounting an immune response. Their deregulation might therefore precede an abnormal T cell response as shown for example by increased Th17 cell frequency and facilitate the onset of autoimmune phenomena such as irAE. Acknowledgements: This work was supported by DFG grants SK59/09–1 and Schu1683/10–1, and by BMBF Project Arthromark 01EC1401B. Disclosure of interest: None declared